Splice-switching as cancer therapy. (August 2021) - Jbara, Amina; Siegfried, Zahava; Karni, Rotem
Abstract: In light of recent advances in RNA splicing modulation as therapy for specific genetic diseases, there is great optimism that this approach can be applied to treatment of cancer as well. Dysregulation of alternative RNA splicing is a common aberration detected in many cancers and thus, provides an attractive target for therapeutics. Here, we present and compare two promising approaches that are currently being investigated to manipulate alternative splicing and their potential use in therapy. The first strategy makes use of splice-switching oligonucleotides, whereas the second strategy uses CRISPR (clustered regularly interspaced short palindromic repeat Cas (CRISPR-associated) technology. We will discuss both the challenges and limitations of these technologies and progress being made to implement splice-switching as a potential cancer therapy.